Lightning Electromagnetics. Volume 1, - Cooray, Vernon; Rachidi, Farhad, 1962-; Rubinstein, Marcos, 1960- (The Institution of Engineering and Technology, 2022)
"Lightning is important for all scientists and engineers involved with electric installations. It is gaining further relevance since climate warming is causing an increase in lightning strikes, and since the rising numbers of renewable power generators, the electricity grid, and charging infrastructure are susceptible to lightning damage. This is the second edition to this comprehensive work."--Provided by publisher.
Keywords: Lightning.; Electromagnetism.; Electromagnetic waves.; elektronické knihy; electronic books